2015
DOI: 10.1038/bmt.2014.324
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid memory T-cell reconstitution recapitulating CD45RA-depleted haploidentical transplant graft content in patients with hematologic malignancies

Abstract: T-cell depletion of an HLA-haploidentical graft is often used to prevent graft-vs.-host disease (GvHD), but the procedure may lead to increased graft failure, relapse, and infections due to delayed immune recovery. We hypothesized that selective depletion of the CD45RA+ subset can effectively reduce GvHD through removal of naïve T cells, while providing improved donor immune reconstitution through adoptive transfer of CD45RA– memory T cells. Herein, we present results from the first 17 patients with poor-progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 46 publications
2
89
0
2
Order By: Relevance
“…Ex vivo depletion of CD45RA + T-cells and adoptive transfer of CD45RA-memory T cells hasten the immune reconstitution post-transplant, enhances the GVL effect while abrogating GVHD. This strategy was recently evaluated in a study of 17 adults with high risk hematologic malignancies (16 AML and 1 myelodysplasia) with KIR receptor-ligand mismatched haploidentical donor[38]. The conditioning regimen included total lymphoid irradiation (8 Gy), fludarabine (150 mg/m 2 ), cyclophosphamide (60 mg/kg), thiotepa (10 mg/kg) and melphalan (140 mg/m 2 ).…”
Section: Haploidentical Stem Cell Transplant Strategiesmentioning
confidence: 99%
“…Ex vivo depletion of CD45RA + T-cells and adoptive transfer of CD45RA-memory T cells hasten the immune reconstitution post-transplant, enhances the GVL effect while abrogating GVHD. This strategy was recently evaluated in a study of 17 adults with high risk hematologic malignancies (16 AML and 1 myelodysplasia) with KIR receptor-ligand mismatched haploidentical donor[38]. The conditioning regimen included total lymphoid irradiation (8 Gy), fludarabine (150 mg/m 2 ), cyclophosphamide (60 mg/kg), thiotepa (10 mg/kg) and melphalan (140 mg/m 2 ).…”
Section: Haploidentical Stem Cell Transplant Strategiesmentioning
confidence: 99%
“…Following the completion of conditioning, patients received a graft composed of CD34-selected PBSCs (≥5 × 10 If randomized trials confirm the substantial reduction in cGVHD with T N depletion observed in our trial, without impairment of other important HCT outcomes, this approach could be used at most HCT centers. During the period of patient accrual in our trial, 3 small pilot studies of T N depletion in recipients of HLA-mismatched or haploidentical HCT were initiated at other centers and published (59)(60)(61). Two of these studies administered antithymocyte globulin or alemtuzumab to provide additional TCD (59,60), and the third study incorporated total lymphoid irradiation in the conditioning regimen and NK cell infusions after HCT (61).…”
Section: Methodsmentioning
confidence: 99%
“…During the period of patient accrual in our trial, 3 small pilot studies of T N depletion in recipients of HLA-mismatched or haploidentical HCT were initiated at other centers and published (59)(60)(61). Two of these studies administered antithymocyte globulin or alemtuzumab to provide additional TCD (59,60), and the third study incorporated total lymphoid irradiation in the conditioning regimen and NK cell infusions after HCT (61). The small sizes of these studies; differences in the patient populations, donor sources, and conditioning; and the inclusion of T celldepleting antibodies, total lymphoid irradiation, or additional cell infusions preclude comparisons of the reported patient outcomes with the results of our trial.…”
Section: Methodsmentioning
confidence: 99%
“…These include addback of ex vivo allodepleted T cells and na€ ıve T cell depletion of stem cell products via CD45RA or TCRa/b depletion. [111][112][113] Incorporation of safety switches into T cells prior to infusion allows selective deletion of genemodified cells if GVHD occurs. 114,115 Other immunomodulatory approaches to GVHD include induction of anergy or administration of regulatory T cells but the effect of these strategies on CMV immunity has not been studied.…”
Section: Engineering Of the Graft To Improve Immune Recoverymentioning
confidence: 99%